Effect of oxygen on the mechanism of phase-structural transformations in O-Containing titanium hydride. (20th September 2019) - Suwarno, S.; Maehlen, J.P.; Denys, R.V.; Yartys, V.A.
Abstract: Titanium hydride is a well characterized binary hydride which is used as a high temperature H storage material. Detailed studies on hydrogen absorption and desorption kinetics in titanium, as well as phase transformations in the Ti-based hydrides are important to achieve reversibility of H storage and their efficient use. As oxygen forms a solid solution in titanium metal, this affects the mechanism of its hydrogenation and dehydrogenation. In the present work, we have studied the hydrogenation and dehydrogenation of titanium containing a variable amount of oxygen, 1.8 wt% and 3.0 wt%. A detailed study of the phase-structural transformations in O-containing Titanium-Hydrogen system was performed using in situ synchrotron X-ray diffraction. This study showed that they proceed via the following reaction pathway Ti(O)→δ→β→δ−ΤιΗ2 →ε-TiH2 . The δ→ε transformation was studied by monitoring the splitting of the (110) peak of the δ phase into the (110) and (002) peaks of the ε phase. This transformation starts at 25 °C with a slight lattice expansion occurring during the cooling and isothermal holding. It is found that after the rehydrogenation, oxygen becomes segregated to form an oxygen-rich α-Ti-based phase and Ti-based hydrides, and the extent of segregation increases with increasing oxygen concentration in the initial titanium metal. A reduction of the lattice parameters of TiH2 proceeds after accomplishing one hydrogen absorption-desorption-absorption cycle indicating a decrease in H/Ti ratio occurring within the homogeneity region of the dihydride TiH<2 . Graphical abstract: Image 1 Highlights: In situ SR-XRD study of H absorption-desorption in oxygen-containing titanium. Oxygen is dissolved in the hexagonal α-Ti but not in Ti hydride. The mechanism of transformations on H abs-des is defined by O content. For TiH2 with bulk oxygen content of 3.1 wt% δ → ε transformation starts at 25 °C. Low temperature transformation δ-ΤιΗ2 .→ε-TiH2 has been characterized in detail